2010
DOI: 10.1007/s10236-010-0346-7
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal circulation and influence factors of the Bohai Sea: a numerical study based on Lagrangian particle tracking method

Abstract: Seasonal circulation of the Bohai Sea (BS) in 1992 was investigated using Lagrangian particle tracking method. The hydrography of the BS was simulated based on an unstructured grid, finite-volume, three-dimensional primitive equation ocean model. With the use of the unstructured triangular grid, the model can easily fit the irregular coastal boundary of the BS. The simulated tides, tidal current, and thermohaline field agreed well with the observations. The transport of particles has three-dimensional structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 18 publications
1
25
0
Order By: Relevance
“…Previous studies suggested the importance of baroclinic structure to the basin-scale gyre (Liang et al, 2006;Wang et al, 2010) and the importance of anti-cyclonic flow in the central Bohai Sea . In comparison, our climatological simulations reveal that the Bohai Sea circulation is characterized by a basin-scale cyclonic gyre and a few co-existing eddy-like structures from May to…”
Section: Lagrangian Particle-tracking Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies suggested the importance of baroclinic structure to the basin-scale gyre (Liang et al, 2006;Wang et al, 2010) and the importance of anti-cyclonic flow in the central Bohai Sea . In comparison, our climatological simulations reveal that the Bohai Sea circulation is characterized by a basin-scale cyclonic gyre and a few co-existing eddy-like structures from May to…”
Section: Lagrangian Particle-tracking Experimentsmentioning
confidence: 99%
“…Monsoon wind plays an overwhelming role on the circulation in winter (Miao and Liu, 1988), while the rather weak winds in summer plays a less important role in driving the circulation except at the surface (Zhao and Shi, 1993). Recent modeling studies suggested the importance of a horizontal density gradient to the basin-scale gyre (Liang et al, 2006;Wang et al, 2010). Using a diagnostic model, Wan et al (2004) recognized the significance of density-driven circulation using a set of experiments based on a hydrographic survey conducted in August 2000.…”
mentioning
confidence: 99%
“…Wuxing Lake is a shallow lake with small areas and irregular shapes. Unstructured grids [11,[21][22][23] were used here to fit the complicated lake boundaries better. There were altogether 1213 grids of an average size of 10m10m and 765grid nodes.…”
Section: Model Configurationmentioning
confidence: 99%
“…The Bohai Sea is a semi-enclosed embayment on the coast of China in the northwest Pacific Ocean, and its tidal system has been well documented from observations and hydrodynamic model simulations [23][24][25]. The test data set for this case consists of M 2 , K 1 , S 2 , and O 1 tidal constituents from 31 observed tidal stations in the Bohai Sea [23], of which 29 are near the coast, and two are from islands in the mouth of the Bohai Sea.…”
Section: Tides In the Bohai Seamentioning
confidence: 99%